PRINSIP KERJASAMA, KESOPANAN, DAN IRONI DALAM MASYARAKAT JEPANG: SEBUAH TINJAUAN DARI DIMENSI SOSIOPRAGMATIS - Eman Suherman (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
When speech act is practiced by human being, there are always figures or roles involved in it. They are a speaker and a listener. The existence of two parties, language usage is not only related textually but also interpersonal matters. Language is not only a pragmatically textual retorica but also as a pragmatically interpersonal retorica.As an interpersonal retorica, language has methods or principles. The division made by Halliday, Geoffrey Leech divides interpersonal retoric into three kinds of principles namely Cooperative Principle, Politeness Principle, and Irony Principle.The three principles are clearly shown by Japanese society. In Japanese society social status and friendship are absolute and well reflected in the language. Japanese supports, this social system through the use of smooth language known as Keigo. For Japanese people it is vital to know how to determine differences of social status and this fiendship and admit it as reflected in the usage of Keigo.